The phenomenom of the death of expertise: the use of social media by teenagers from the persfective of the quran surah an- nahl 43 - Efa Nurazizah; Patria Yunita (At Turots: Jurnal Pendidikan Islam, 2026)
This studi discusses the phenomenom of the death of the expertise among teenagers by social media. Indonesia continues to experience an increase in internet usage from 62% in 2018 to 72.80% in 2024, with social media users reaching 50.2% of the total population (30% of these users are teenagers). This trend is an invaluable resource for marketers, business people, content developers, and anyone seeking to understand and harness Indonesia's digital potential. However, the ease of accessing information on social media, if not accompanied by a passion for understanding the truth, can lead to confirmation bias among teenagers. This occurs because expertise on social media is viewed skeptically and its presence is eclipsed by populism. A lack of critical thinking is one of the causes of the demise of expertise among teenagers. The flood of information on social media makes them unable to distinguish fact from fiction. The Quran, Surah An-Nahl, 16:43, teaches us the importance of a teacher/expert/specialist as a source of guidance for questions and doubts. By reasoning amidst low digital literacy, it is hoped that teenagers will be able to distinguish between fact and fiction, positive and negative